(untitled) (diségno, 2025)
Issue No. 16 of the journal diségno marks the handover of a scientific publication founded in 2017 and which has been running for 8 years. A balance sheet full of events and transformations, which now sees a mature journal witnessing the scope of a scientific disciplinary sector with strong ties to Area 08 - Civil Engineering and Architecture and beyond. [read more]